2020
DOI: 10.5191/jiaee.2020.273132
|View full text |Cite
|
Sign up to set email alerts
|

Awakening Transformative Learning: A Comparison of the Dissonance Experienced by Agriculture Majors During Study Abroad Courses to Costa Rica and Thailand

Abstract: Students who have participated in study abroad courses exhibit an improved capacity for citizenship, emotional growth, and global competence. However, achieving such requires that study abroad courses be designed to allow students to question their underlying beliefs and values – a concept called dissonance. When individuals reflect on dissonance, it has been reported to spur a process in which their previously held perspectives are transformed. As such, this investigation sought to compare the dissonance expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…For instance, during a study abroad course to Nicaragua, students encountered four forms of dissonance -environmental, sociocultural, intellectual, and personal -that influenced the transformation in perspectives that students endured (O'Malley et al, 2019). However, in a comparison of the dissonance experienced by agriculture majors during international experiences to Costa Rica and Thailand, Pigg et al (2020) argued the dissonance students encountered appeared to be influenced by the context and duration of their study abroad course, which provided deeper insight into why students may experience variant shifts in perspectives in literature. Although some previous work (Roberts & Edwards, 2015, 2016 has explored whether these transformations are integrated into students' lives after returning home, more knowledge is needed to distill the long-term outcomes of study abroad courses.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, during a study abroad course to Nicaragua, students encountered four forms of dissonance -environmental, sociocultural, intellectual, and personal -that influenced the transformation in perspectives that students endured (O'Malley et al, 2019). However, in a comparison of the dissonance experienced by agriculture majors during international experiences to Costa Rica and Thailand, Pigg et al (2020) argued the dissonance students encountered appeared to be influenced by the context and duration of their study abroad course, which provided deeper insight into why students may experience variant shifts in perspectives in literature. Although some previous work (Roberts & Edwards, 2015, 2016 has explored whether these transformations are integrated into students' lives after returning home, more knowledge is needed to distill the long-term outcomes of study abroad courses.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We conclude that students' lived experiences during the study abroad trip exposed them to forms of high-intensity dissonance that made them more deeply ponder the implications of social inequities in the world. Although previous literature (O'Malley et al, 2019, Pigg et al 2020 has reported that university agriculture students experienced some shortterm shifts in perspective in this regard, scant evidence exists in the literature on agriculture…”
Section: Figurementioning
confidence: 99%
“…We recommend that faculty make existing cultural systems, ideologies, and structures of power visible for students during study abroad courses. Such phenomena appeared to help students make sense of the differences between Nicaragua and Louisiana in the current study (O'Malley et al, 2019;Pigg et al, 2020). Perhaps to make these power dynamics more accessible for students, faculty could embed approaches that seek to illuminate norms and traditions that are often less tangible and difficult for students to grasp (Hartman & Kiely, 2014).…”
Section: Purpose and Objectivesmentioning
confidence: 97%
“…For instance, during a study abroad course to Nicaragua, students encountered four forms of dissonance -environmental, sociocultural, intellectual, and personal -that influenced the transformation in perspectives that students endured (O'Malley et al, 2019). However, in a comparison of the dissonance experienced by agriculture majors during international experiences to Costa Rica and Thailand, Pigg et al (2020) argued the dissonance students encountered appeared to be influenced by the context and duration of their study abroad course, which provided deeper insight into why students may experience variant shifts in perspectives in literature. Although some previous work (Roberts & Edwards, 2015 has explored whether these transformations are integrated into students' lives after returning home, more knowledge is needed to distill the long-term outcomes of study abroad courses.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…However, Wibulswasdi et al (2012) argued the most important change occurred in its agricultural system. A need emerged, therefore, to better understand how the investments to human capital through SEP led to a reenvisioned agricultural system in Thailand (Pigg et al, 2020).…”
Section: Introduction and Problem Statementmentioning
confidence: 99%